Experimental Heat Transfer Enhancement in a Tubular Heat Exchanger - Osman, Abdelbagi; Hassan, Rasha; Sulman, Abdalla; Mahajoub, and Imad (Gezira Journal of Engineering and Applied Sciences, 2018)
Heat exchange process is one of the fundamental subjects in chemical and food process industries. This research investigates an experimental study to enhance the heat transfer process in tubular (water-to-water) heat exchanger. Two typical sets of experiments have been conducted using a horizontal double pipe (tubular) heat exchanger. The first set was conducted for the existing apparatus as installed at different fluids flow patterns for parallel and counter flow arrangement. The second experiment had been done after inserting a coiled copper wire in the inner pipe that containing a fluid of hot water. The obtained results from both experiment sets were compared. It is found that the tube insert has tremendously affected the performance of the exchanger and showed a noticeable enhancement. The tube inserts forces the flow to be more turbulent that indicated by the increased value of Reynold’s number ( Re ) to reach 3364 in some flow patterns. Consequently, the overall heat transfer coefficient has also enhanced in some cases from 517.31 to 981.93 W/m 2 . o C for parallel flow and from 750.18 to 1105 W/m 2 . o C for countercurrent flow. Furthermore, one of the exchanger effectiveness reading has increased from 25% to 43.9%.